Perception of the quality of life of older adults of Borba-AM, Brazil (Research, Society and Development, 2022)
Quality of life is a multidimensional concept that refers to an individual's perception of their position in life in the context of the culture and value system in which they live and in relation to their goals, expectations and standards and is affected by their physical health and the psychological state. This study aimed to describe the perception of health-related quality of life of elderly people living in the municipality of Borba-AM, Brazil. The sample consisted of 233 elderly people (71.2 ± 8.9 years). The data were obtained through the generic instrument of quality of life "Medical Outcomes Study 36-Item Short-Form Health Survey" (SF-36). It is verified that the domains: functional capacity, pain, general health, vitality and social aspects had higher and statistically significant values (p